(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The essay focuses on organ donation as a possible choice for those patients seeking euthanasia or assisted suicide whose informed and free consent has to be carefully preserved. In that case, indeed, concern for the welfare of others, on the one hand, and dying for having relief from illness, on the other hand, could confusedly converge in the will of a vulnerable person receiving medical treatments. The Dutch and the Belgian statutory frameworks governing organ donation after euthanasia can shed light on this such ethical theme involving human dignity that should be ignored by the Italian legislator anymore.